What are the radiographic prevalence and anatomical patterns of maxillary sinus septa in a Turkish cohort? - Ibrahim Burak Yuksel; Sumeyye Celik Ozsoy; Muhammet Emin Arslan; Fatma Altiparmak; Hatice Yilmaz; Ali Altindag; Guldane Magat (BMC Oral Health)
Abstract Background The maxillary sinus may contain cortical bony partitions, called Underwood’s septae, which protrude into the sinus cavity and can subdivide it into multiple compartments. These structures are often shaped like inverted gothic arches and may be overlooked on routine imaging. However, their presence can significantly affect surgical access and outcomes, particularly in posterior maxilla procedures. Early identification of such anatomical variations contributes to safer and more predictable treatment planning. Aim This study aimed to determine the prevalence and anatomical characteristics of maxillary sinus septae in a Turkish adult population by evaluating digital panoramic radiographs. Methods Panoramic radiographs of 1000 patients (587 females and 413 males), aged between 18 and 70 years, were retrospectively analyzed. The sample consisted of patients who visited the Department of Oral and Maxillofacial Radiology at Necmettin Erbakan University Faculty of Dentistry. Maxillary sinus septa are defined as bony extensions from the sinus walls that rise at least 2.5 mm high, as noted by Velasquez Plata et al. According to Underwood’s anatomical descriptions, their position within the sinus cavity is categorized as anterior, middle, or posterior. These established criteria support the reliable identification and localization of septa, which is crucial for evaluating surgical risks and planning interventions in the maxillary sinus. All findings were recorded based on gender, lateralization (unilateral/bilateral), crest status (dentate/edentulous), and side (right/left). Statistical analyses were performed using SPSS version 21.0, with significance at p < 0.05. Results Among the 1000 radiographs, 529 revealed at least one maxillary sinus septum, yielding a prevalence rate of 52.9%. A total of 748 septa were identified, with unilateral septa in 385 patients and bilateral in 144. In 587 female patients (1174 sinuses), 428 septa were detected, while in 413 male patients (826 sinuses), 320 septa were observed. The prevalence was slightly higher in males (53.75%) compared to females (52.29%). Most septae were located in the posterior region, followed by the middle and anterior regions. The statistical analysis confirmed the findings were significant (p < 0.05). Conclusion Digital panoramic radiography is valuable for identifying anatomical variations such as maxillary sinus septae. Preoperative recognition of these structures is crucial in reducing surgical risks, particularly in sinus lift and implant procedures. Radiologists and oral surgeons should be vigilant in detecting septae to ensure safe and effective treatment planning. Ethical approval was obtained from the Ethics Committee of Necmettin Erbakan University, Faculty of Dentistry (Date: 31.10.2024; Decision No: 2024/495).